Associations between ambient particle radioactivity and lung function. (September 2019) - Nyhan, Marguerite M.; Rice, Mary; Blomberg, Annelise; Coull, Brent A.; Garshick, Eric; Vokonas, Pantel; Schwartz, Joel; Gold, Diane R.; Koutrakis, Petros
Abstract: Previous studies have suggested increased risk of respiratory diseases and mortality following short-term exposures to ionizing radiation. However, the short-term respiratory effects of low-level environmental radiation associated with air pollution particles have not been considered. Although ambient particulate matter (PM) has been reproducibly linked to decreased lung function and to increased respiratory related morbidity, the properties of PM promoting its toxicity are uncertain. As such, we evaluated whether lung function was associated with exposures to radioactive components of ambient PM, referred to as particle radioactivity (PR). For this, we performed a repeated-measures analysis of 839 men to examine associations between PR exposure and lung function using mixed-effects regression models, adjusting for potential confounders. We examined whether PR-lung function associations changed after adjusting for PM2.5 (particulate matter≤2.5 μm) or black carbon, and vice versa. PR was measured by the USEPA's radiation monitoring network. We found that higher PR exposure was associated with a lower forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV1 ). An IQR increase in 28-day PR exposure was associated with a 2.4% lower FVC [95% confidence interval (CI): 1.4, 3.4% p  < 0.001] and a 2.4% lower FEV1 (95% CI: 1.3, 3.5%, p  < 0.001). The PR-lung function associations were partially attenuated with adjustment for PM2.5 and black carbon. This is the first study to demonstrate associations between PR and lung function, which were independent of and similar in magnitude to those of PM2.5 and black carbon. If confirmed, future research should account for PR exposure in estimating respiratory health effects of ambient particles. Because of widespread exposure to low levels of ionizing radiation, our findings may have important implications for research, and environmental health policies worldwide. Highlights: Particulate matter (PM) adversely affects lung function but factors promoting its toxicity are uncertain. The respiratory effects of low-level environmental radioactivity from PM are unknown. We evaluate how particle-bound radioactivity (PR) is associated with lung function. Independent of PM, we demonstrate that PR is associated with decreased FVC and FEV1 . Our findings will have important implications for research and environmental health policy.